GEOCHEMICAL CHARACTERISTICS OF THE MODERN STATE OF SALT LAKES IN ALTAI KRAI - Leonova G.A.; Bobrov V.A.; Bogush A.A.; Anoshin G.N.; Bychinskii V.A. (My University, 2007)
A complex of analytical methods (atomic absorption spectroscopy AAS, synchrotron radiation X-ray fluorescence SR-XRF, and instrumental neutron activation analysis INAA) were used for analyses of 40 trace elements. In compliance with the conventional biogeochemical methods, enrichment factors EF were calculated for plankton relative to the average concentrations of elements in continental clay (shale) preliminarily normalized to Sc. In order to understand the concentration specifics of trace elements in living organisms inhabiting aquatic ecosystems of variable salt composition and geochemical characteristics, chemical speciation of elements was calculated for the brines of salt lakes by the WATEQ4F and Selektor-S computer programs. The enrichment of plankton in Hg in Lake Bol'shoe Yarovoe is caused not only by the chemistry of the mineralized brine (bittern), as follows from the Hg speciation in it, but also by anthropogenic contamination (Hg-bearing wastes from the Altaikhimprom chemical plants in the town of Yarovoe). © Pleiades Publishing, Ltd. 2007.